Share and contract tapping in rubber smallholdings in Peninsular Malaysia - Chew, Tek Ann; Fee, Wang Leong (1985)
The land tenuire literature classifies land tenure into three main tvpes: fixed rent system: sharecropping: and. wage system. In Chinese rubber smallholdings in Peninsular Malaysia. the predominant tenure tapping system is the sharecropping system – either share tapping or its variant contract tapping. This paper outlines a transactional fromework to explain the rationale and prevalence of share and contract tapping. Eight hypotheses were postulated from the framework regarding size of loadings. monitoring or tappers. yield productivity,f ertiliser income earned and possible future imparlance of share and contract tapping.